2018
DOI: 10.1111/joic.12541
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage closure with the Ultraseal device: Initial experience and mid‐term follow‐up

Abstract: Our results suggest that the Ultraseal device is a feasible option for LAA occlusion. Notably, the learning curve in this registry was fast, paralleled by extremely low complication rates. These results should be considered hypothesis generating and larger studies are mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…One patient presented device related thrombus without clinical consequences. Another study in 23 consecutive patients with NVAF has also demonstrated a high success rate of implantation (21/23) and extremely low complication rate at a mean follow-up of 166 ± 80 days [100]. In a multicenter experience of 126 patients from 15 Canadian and European centers [101], this device was successfully implanted in 97% of patients, and major periprocedural adverse events (pericardial effusion, stroke, or device embolization) occurred in only three (2.4%) patients.…”
Section: Ultraseal Devicementioning
confidence: 83%
“…One patient presented device related thrombus without clinical consequences. Another study in 23 consecutive patients with NVAF has also demonstrated a high success rate of implantation (21/23) and extremely low complication rate at a mean follow-up of 166 ± 80 days [100]. In a multicenter experience of 126 patients from 15 Canadian and European centers [101], this device was successfully implanted in 97% of patients, and major periprocedural adverse events (pericardial effusion, stroke, or device embolization) occurred in only three (2.4%) patients.…”
Section: Ultraseal Devicementioning
confidence: 83%
“…DRT was found in one patient, without clinical consequences. Another study in 23 consecutive NVAF patients also demonstrated high success rate of implantation (21/23) and extremely low complication rate at a mean follow-up of 166 80 days [ 94 ]. In multicenter experience of 126 patients from 15 Canadian and European centers [ 95 ] the device was successfully implanted in 97% of patients, with major periprocedural adverse events (pericardial effusion, stroke, device embolization) occurring in only 3 (2.4%) instances.…”
Section: Laao Devicesmentioning
confidence: 98%
“…Timelines of device preclinical, United States Food and Drug Administration (US FDA) and Conformité Européenne (Commercial Sale of Licensed Product in the EU) (CE-Mark) approval, and main relevant studies are summarized in Table 1 (Ref. [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ]).…”
Section: Laao Devicesmentioning
confidence: 99%
“…28 Another smaller, single-center study by Pagnotta et al also reported on the feasibility and safety of the Ultraseal device in their experience based on 23 patients with a mean follow-up of 166 days ± 80 days. 29…”
Section: Ultrasealmentioning
confidence: 99%